Penggunaan Narkotika dan Psikotropika sebagai Media Pengobatan Menurut Pandangan Islam - Muhammad Zaky Athallah; Akila Rama Izza; Faris Abiy Rizky (VitaMedica : Jurnal Rumpun Kesehatan Umum, 2024)
Narcotics and psychotropics are two classes of dangerous drugs that are often abused. The number of users of these two drugs in Indonesia has increased significantly. The purpose of writing this article is to review the use of narcotics and psychotropic substances as a medium of treatment according to Islam. There are several narcotic and psychotropic drugs that can be used medically, including codeine, morphine, methadone, diazepam, alprazolam, methylphenidate, and others. In Islam, narcotics and psychotropic substances are associated with khamr and are absolutely forbidden. However, the use of these two classes of drugs is permitted in emergency conditions.